Pengembangan Bahan Ajar Problem Based Learning pada Materi Thaharah di Mts 1 Ogan Ilir - murtosiah, siti; Zulaiha, Andini (Program Studi Pendidikan Agama Islam IAIQI Al-Qur'an Al-Ittifaqiyah, 2023)
The purpose of this study is to develop a fiqh teaching material for class VII based on Problem Based Learning. Type of research and development using the ADDIE development model (analysis, design, development, implementation, and evaluation). The evaluation location of the teaching materials developed is at MTs Negeri 1 Ogan Ilir. Data collection techniques use observation,The results of this study are: 1) The level of validity of teaching materials developed in the category is very valid. Material experts give a score of 4.6 which means very valid, design experts give a score of 4.3 which means very valid and linguists give a score of 4.4 which means very valid. 2) The level of practicality of teaching materials is measured through the implementation stage of one to one and small group. From the one to one stage, an average score of 4.25 was obtained, which means it was very practical, while in the small group stage, an average score of 4.29 was very practical. 3) The level of effectiveness of teaching materials is evaluated in class through pretest and post test evaluations. From the pretest evaluation, an average score of 58.82 was obtained and the percentage of students who passed KKM was 35.48%. As for the post test score, the average score of students was 86.47 and the percentage of students who passed KKM was 87.09%. From these results, it shows that teaching materials fall into the category of very effective.